The answer to the mathematical problem 6 times 2/3 is 4. This is solved by turning the whole number 6 into a fraction (6/1), multiplying the numerators together (6 times 2 equals 12), multiplying the denominators together (1 times 3 equals 3), and putting the new numerator over the new denominator (12/3), which simplifies to 4.
The question is asking you to multiply 6 by 2/3. Let's follow the steps to solve this multiplication problem.
So, 6 times 2/3 equals 4.
#SPJ2
Answer:
(4,5)
Step-by-step explanation:
Given that M is the midpoint of the Line RS. Where the coordinates of M, R and S are
M(5,7)
R(X,Y)
S(6,9)
Here we have to find the valuer of X and Y
We will use the mid point formula which is given below.
Let put the coordinated of M and S and find coordinates of R
Hence our coordinates are
(4,5)
The midpoint of the line is the point that divides in two halves of the same length.
Reasons:
The given parameters are;
The midpoint of AB in parallelogram ABCD = E
The midpoint of DC = F
Point of intersection of EF and DB = Point G
Required:
To prove that point G is the midpoint of EF.
Solution:
Statement Reason
1. m∠BDC ≅ m∠ABD 1. Alternate angles theorem
2. m∠DGF ≅ m∠BGE 2.Vertical angles theorem
3. = 3. Opposite sides of a parallelogram ABCD
4. ≅ 4. Definition of midpoint of DC
5. = 5. Definition of congruency
6. + = DC 6. Segment addition property
7. + = DC 7. Substitution property
8. 2· = DC 8. Addition
9. = 0.5· = 9. Division property
Similarly;
10. = 0.5· = 10. Division property
11. 0.5· = 0.5· 11. Multiplication property of equality
12. = 12. Substitution property
13. ΔDFG ≅ ΔBGE 13. Angle-Angle-Side rule of congruency
14. ≅ 14. CPCTC
15. = 15. Definition of congruency
16. Point G is the midpoint of 17. Definition of midpoint
Learn more about the midpoint of a line here:
Answer:
GF = GE that prove G is the mid-point of EF
Step-by-step explanation:
In the Parallelogram ABCD
∵E is the mid-point of AB
∵F is the mid-point of CD
∵AB = CD opposite sides in the parallelogram
∴EB = DF⇒(1)
∵AB // CD opposite sides in the parallelogram
∴m∠EBD = m∠FDB alternate angles ⇒(2)
∵BD intersects EF at G
∴m∠BGE = m∠DGF vertically opposite angles ⇒(3)
By using (1) , (2) and (3) you can prove:
ΔBGE is congruent to ΔDGF ⇒ AAS
∴GF = GE
∴G is the mid-point of EF
x-y=0
I have to solve by elimination.
Will someone help me please?
Answer: Find the probability that the number x of correct answers is fewer than 4 = 0.6087
Step-by-step explanation: Please find the attached files for the solution